Agrarian Conflict between Jambi Transmigrant Farmers and PT. Kaswari Unggul: A Social Historical Perspective - Yandi Syahputra Hasibuan; Mujahid Widian Saragih; Jean Ari Hasibuan; Andry Anshari; Suhamri Nasution; Zubaidah Tambunan (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This study examines the agrarian conflict between transmigrant farmers in Jambi Province and PT. Kaswari Unggul from a social-historical perspective. The research investigates how the New Order's transmigration policy in the 1980s shaped patterns of land ownership, social change, and agrarian tension in Sukamaju Village, East Tanjung Jabung Regency. Using a critical historical approach combined with qualitative case studies, the data were collected through in-depth interviews, contemporary media analysis, and literature review. The findings reveal that the transmigration program, initially designed to promote equitable population distribution and agricultural productivity, instead generated structural inequalities and land disputes between local communities and private plantation companies. The state's developmental agenda, framed within modernization and economic growth narratives, failed to protect the rights and welfare of transmigrant farmers. The persistence of agrarian conflicts illustrates the long-term social impact of the New Order’s policies, which continue to influence rural dynamics and peasant struggles in Jambi today.